Pendampingan Literasi Dan Numerasi Anak Usia Sekolah Dasar Di Padang Cermin, Langkat, Sumatera Utara - Ginting, Cica Ayu Astria Br; Saputri, Lilis; Mardiana, Mardiana; Sitepu, Dewi Rulia Br; Afni, Khairina; Devieta, Alviona; Dinanti, Ivo; Tarigan, Silviyana Br (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The community service program aims to: 1) improve the literacy and numeracy of elementary school-age children; 2) reduce the addiction of elementary school-aged children to playing online games; and 3) help parents pay more attention to their children's learning of literacy and numeracy in Padang Cermin Village. The form of community service activities is carried out by making tutoring in literacy and numeracy available. The subjects of the service are elementary school-age children and their parents. Activities are carried out in stages, including planning, observation, technical implementation, program implementation, and evaluation. The results of community service obtained have succeeded in: 1) improving the literacy and numeracy abilities of elementary school-aged children; 2) reducing the addiction of elementary school-aged children to playing online games; and 3) helping parents pay more attention to their children's learning of literacy and numeracy in Padang Cermin Village.